cis-Aconitic Acid, a Constituent of Echinodorus grandiflorus Leaves, Inhibits Antigen-Induced Arthritis and Gout in Mice - de Oliveira, Diego Pinto; Garcia, Eliana de Faria; de Oliveira, Mariana Assíria; Candido, Luiza C. M.; Coelho, Fernanda M.; Costa, Vivian Vasconcelos; Batista, Nathália Vieira; Queiroz-Junior, Celso Martins; Brito, Larissa Froede; Sousa, Lirlândia Pires; Souza, Daniele G.; Amaral, Flávio Almeida; de Pádua, Rodrigo Maia; Teixeira, Mauro Martins; Braga, Fernão Castro (Planta Medica, 2021)
cis-Aconitic acid is a constituent from the leaves of Echinodorus grandiflorus, a medicinal plant traditionally used in Brazil to treat inflammatory conditions, including arthritic diseases. The present study aimed to investigate the anti-arthritic effect of cis-aconitic acid in murine models of antigen-induced arthritis and monosodium urate-induced gout. The possible underlying mechanisms of action was evaluated in THP-1 macrophages. Oral treatment with cis-aconitic acid (10, 30, and 90 mg/kg) reduced leukocyte accumulation in the joint cavity and C-X-C motif chemokine ligand 1 and IL-1β levels in periarticular tissue. cis-Aconitic acid treatment reduced joint inflammation in tissue sections of antigen-induced arthritis mice and these effects were associated with decreased mechanical hypernociception. Administration of cis-aconitic acid (30 mg/kg p. o.) also reduced leukocyte accumulation in the joint cavity after the injection of monosodium urate crystals. cis-Aconitic acid reduced in vitro the release of TNF-α and phosphorylation of IκBα in lipopolysaccharide-stimulated THP-1 macrophages, suggesting that inhibition of nuclear factor kappa B activation was an underlying mechanism of cis-aconitic acid-induced anti-inflammatory effects. In conclusion, cis-aconitic acid has significant anti-inflammatory effects in antigen-induced arthritis and monosodium urate-induced arthritis in mice, suggesting its potential for the treatment of inflammatory diseases of the joint in humans. Additionally, our findings suggest that this compound may contribute to the anti-inflammatory effect previously reported for E. grandiflorus extracts.
Keywords: cis-aconitic acid; rheumatoid arthritis; gout; complete Freundʼs adjuvant; Echinodorus grandiflorus; Alismataceae; NFκB